The minimum wage, turnover, and the shape of the wage distribution - Pierre Brochu; David A. Green; Thomas Lemieux; James Townsend (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2023)
This paper proposes an empirical approach to decompose the distributional effects of minimum wages into effects for workers moving out of employment, workers moving into employment, and workers continuing in employment. We estimate the effects of the minimum wage on the hazard rate for wages, which provides a convenient way of re-scaling the wage distribution to control for possible employment effects. We find that minimum wage increases do not result in an abnormal concentration of Job Leavers below the new minimum wage, which is inconsistent with employment effects predicted by a neoclassical model. We also find that, for Job Stayers, the spike and spillover effects of the minimum wage are simply shifted right to the new minimum wage. Our findings are consistent with a model where entry wages are set according to a job ladder, and where firms preserve their internal wage structure due to fairness or internal incentives issues.
Keywords: 330; Mindestlohn; Verteilungswirkung; Lohnstruktur; Beschäftigungseffekt; Dekompositionsverfahren; Kanada